Hydrothermal treatment, pelletization and characterization of oil palm empty fruit bunches as solid fuel. (June 2019) - Ahda, Y; Prakoso, T; Rasrendra, C B; Susanto, H
Abstract: Empty fruit bunch (EFB) is not yet utilized as a solid fuel for boiler due to their physical characteristics such as very bulky, high moisture and potassium contents. The hydrothermal treatment (HT) has been conducted in our research to overcome those problems. HT experiments were conducted in a 2 L digester, with 100 grams of EFB. The liquid to solid ratio was 5:1 mL/g. HT were conducted at temperature of 120, 150, 180, 200, and 220°C, and holding time of 60 minutes. The results indicated that the properties on solid products could be improved using HT, particularly its higher heating value (HHV) of 20.1 MJ/kg (obtained from HT at 180°C) compared to feedstock of 19.68 MJ/kg and commercial pellet of EFB of 13.03 MJ/kg. Pellets made of solid product from HT at 150°C and pelletized at 200 bar were considered to meet the characteristic of commercial pellets.